Reversing the Handedness of Self‐Assembled Porous Molecular Networks through the Number of Identical Chiral Centres. Issue 23 (2nd May 2019) - Tahara, Kazukuni; Noguchi, Aya; Nakayama, Ruri; Ghijsens, Elke; De Feyter, Steven; Tobe, Yoshito
Abstract: Scanning tunnelling microscope observations at the 1‐phenyloctane/graphite interface reveal how chiral structural information at the molecular level is transferred and expressed structurally at the 2D supramolecular level for a porous system. The chirality of self‐assembled molecular networks formed by chiral dehydrobenzo[12]annulene (cDBA) derivatives having three chiral chains and three achiral chains, alternatingly, is compared with those of cDBAs having six chiral chains reported previously. While for all cDBAs homochiral surfaces are formed, their handedness is not simply a reflection of the absolute configuration of the stereogenic centres. Both the number of stereogenic centres as well as the length of the achiral chains determine the supramolecular handedness, providing a deep insight into the supramolecular chirality induction mechanisms at play. Moreover, these cDBAs act to induce chirality in porous networks formed by achiral DBAs. Abstract : Right or left? The centers decide : STM observations at the liquid/graphite interface reveal chirality of self‐assembled porous molecular networks formed by chiral molecules having three chiral and three achiral chains. While homochiral surfaces are formed for all chiral molecules, the number of stereogenic centres and the length of the achiral chains determine the supramolecular handedness.